Performance of Hariana cows in their breeding tract - MATHUR, A K; R S CHAHAL, THE LATE (The Indian Journal of Animal Sciences, 2013)
To asses the economic values and the potential of Hariana cows under village conditions, various economic characters like, seasons of calving, sex ratio of calves born, lactation length, lactation yield, daily milk yield, peak milk yield and association factor between peak yield and lactation yield were studied. The study was based on the records of 1 318 cows which were offered for recording and completed the lactation under Central Herd Registration Scheme. No animal offered for recording was rejected before test. It was observed that there was no calving season and animals calved all through the year, although majority of animals calved during months of March, April and June. The average age at calving was observed as 3.77+-0.03, 5.39+-0.03 , 6.59+-0.03 and 7.57+-0.06 years from first to fourth calving respectively. The average lactation length was 282.67+-1.11, 283.17+-0.90, 280.28+-1.05 and 280.49+-2.27 days from first to fourth lactations respectively. It was 281.94+-0.57 days for all lactations taken together. The average service period was observed as 114.90+-3.69, 113.90+-2.60, 110.52+-3.01/110.05+-6.57 days from first to fourth calving, respectively, and an overall average of 112.71+-1.69 days. The calving interval was observed as 399.60+-3.62, 392.41+-2.58, 390.96+-3.01 and 391.83+-6.41 days between first and second, second and third, third and fourth, fourth and fifth calvings respectively. It was 395.50:+-1.68 days for all taken together. The dry period was observed as 117.62+-3.74. 110.42+-2.63, 110.52+-3.01 and 113.48+-6.26 days after first to fourth calvings respectively. The overall dry period was 112.33+-1.70 days. The study of service period, calving interval and dry period was based on the records of 890 animals. This information about remaining animals under record was not available. The average lactation yield was 1784.31+-19.43. 1 964.43+-18.18, 1 995.44+-19.01 and 1 956.96+-35.91 kg from firstto fourth lactations, respectively, and 1 934.28+- 1 0.83 kg for all lactations taken together. The average daily milk yield was 6.31+-0.06, 6.94+-0.06. 7.12+-0.06 and 6.98+-0.10 kg in first to fourth lactations respectively. It was 6.86+-0.03 kg for all lactations taken together. The average peak yield was 8.78+-0.09, 9.72+-0.07, 10.04+-0.07 and 10.01+-0.13 kg in firstto fourth lactations and 9.65+-0.04 for all lactations taken together. The association factor between peak yield and lactation yield was 203.08+-1.31, 202.09+-0.92, 198.83+-1.03 and 195.41+-2.41 from first to fourth lactations. It was 200.76+-0.60 for all lactations taken together.